Inovasi Mahasiswa KUKERTA terintegrasi UNRI 2022 dalam Pembuatan Makanan Tradisional Konji Barayak terhadap Kegiatan Gotong Royong dan Hari Besar di Kuantan Singini Desa Jake - Hendro Ekwarso; Atiton Martwo Putra; Aulia Yuhani; Aysa Indah Bahri; Farhan Ghafara; Fauzan Damansyara; Fidela Raniah Sawity; Kezia Mayindah; Tira Nadia; Yoga Efendi; Yuliana Sukma Rahayu (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
The journal was created with the aim of providing knowledge about traditional foods typical of Kuantan Singingi Regency, Riau Province. The traditional food is food made from starch, and is called konji barayak. Konji barayak is a culinary from the Kuantan Singingi area, which is usually made during large events such as pacu jalur event. This Konji barayak was also made in the context of implementing mutual cooperation with the community in the Kuantan Singingi area. The shape of this food is like porridge with a chewy texture resembling cendol, plus a sweet coconut milk sauce. In this case, the activities carried out in Jake Village with Kukerta students at the University of Riau carried out mutual cooperation in making a soccer field in Jake Village, this aimed to prepare for a competition made by the youth of Jake Village. Of course, in the process of mutual cooperation, this is interspersed with eating with traditional konji barayak food